Early paravalvular leak after conventional mitral valve replacement: A single‐center analysis. Issue 6 (15th March 2022) - Matteucci, Matteo; Ferrarese, Sandro; Cantore, Cristiano; Mantovani, Vittorio; Pedroni, Giada; Cappabianca, Giangiuseppe; Corazzari, Claudio; Kowalewski, Mariusz; Severgnini, Paolo; Lorusso, Roberto; Beghi, Cesare
Abstract: Introduction: Paravalvular leak (PVL) is a well‐recognized complication after mitral valve replacement (MVR). However, there are only a few studies analyzing leak occurrence and postoperative results after surgical MVR. The aim of this study was to assess the rate and determinants of early mitral PVL and to evaluate the impact on survival. Methods: We performed a retrospective analysis involving patients who underwent MVR from January 2012 to December 2019 at our Institution. Postoperative transthoracic echocardiography evaluation was done for all subjects before hospital discharge. Multivariable analysis was carried out by constructing a logistic regression model to identify predictors for PVL occurrence. Results: Four hundred ninety‐four patients were enrolled. Operative mortality was 4.9%. Early mitral PVL was found in 16 patients (3.2%); the majority were mild (75%). Leaks occurred more frequently along the posterior segment of the mitral valve annulus (62.5%). Only one individual with moderate‐to‐severe PVL underwent reoperation during the same hospital admission. Multivariable analysis revealed that preoperative diagnosis of infective endocarditis was the only factor associated with early leak after MVR (odds ratio: 4.96; 95% confidence interval: 1.45–16.99; p  = .011). Overall mortality at follow‐up (mean follow‐up time: 4.7 [SD: 2.5] years) was 19.6% and favored patients without early mitral PVL. Conclusion: The incidence of early PVL after MVR is low. PVL is usually mild and develop more frequently along the posterior segment of the mitral valve annulus. Preoperative diagnosis of infective endocarditis increases the risk of PVL formation.